2016
DOI: 10.1136/bjsports-2016-096123
|View full text |Cite
|
Sign up to set email alerts
|

‘FIFA 11 for Health’ for Europe. 1: effect on health knowledge and well-being of 10- to 12-year-old Danish school children

Abstract: AimTo modify the ‘FIFA 11 for Health’ programme to the European situation, and to assess its effects on health knowledge and well-being in Danish school children.MethodA two-cohort study with seven intervention and two control schools. Of the 546 Danish children (boys 269; girls 277) of mean age 11.1 (±0.4) years from five city and four country-side schools, 402 undertook the ‘FIFA 11 for Health’ programme and 144 acted as controls. As part of each school's PE curriculum, seven intervention schools received a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 20 publications
5
44
1
Order By: Relevance
“…Thus, the on-pitch education on health knowledge related to food and fluid intake and importance of high-intensity physical training as well as everyday life physical activities such as walking and cycling could have influenced the children's behaviour during the 11-week intervention period. However, further studies are needed to elucidate whether the increases in health knowledge observed following the 'FIFA 11 for Health' programme 7 have resulted in the desired behavioural changes towards better dietary habits and/or more physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the on-pitch education on health knowledge related to food and fluid intake and importance of high-intensity physical training as well as everyday life physical activities such as walking and cycling could have influenced the children's behaviour during the 11-week intervention period. However, further studies are needed to elucidate whether the increases in health knowledge observed following the 'FIFA 11 for Health' programme 7 have resulted in the desired behavioural changes towards better dietary habits and/or more physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…7 The modifications to the physical activity content were based on research on the fitness and health effects of football conducted at the University of Copenhagen. This research has shown that 6-16-week interventions with two weekly 30-60 min sessions of small-sided football provide marked broad-spectrum fitness and health improvements for participants across the lifespan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The Fédération Internationale de Football Association (FIFA) developed a program using football-based exercises to educate children about health, hygiene, and contamination, and to introduce regular physical activity in order for children to gain from the benefits of football practice. 1,17,18 In 2015, Denmark was the first country in Europe to implement the "FIFA 11 for Health" program. The program was modified to meet the health demands of the western world, with a primary focus on reducing the risk of developing NCDs.…”
mentioning
confidence: 99%
“…The program was modified to meet the health demands of the western world, with a primary focus on reducing the risk of developing NCDs. 13,17 The modifications in the physical section of the program were based on studies of football-based exercises showing that 6-to 16-week interventions involving two weekly sessions, lasting 30-60 minutes, of football exercises and 3v3 games, improved the physical health of children and adults. [19][20][21] The modifications in the education section were focused on the themes of physical activity, nutrition, hygiene, and alcohol and tobacco consumption.…”
mentioning
confidence: 99%